A study of integration of LIDAR and photogrammetric data sets by indirect georeferencing and in situ camera calibration. (3rd April 2017) - Costa, Felipe André Lima; Mitishita, Edson Aparecido; Centeno, Jorge Antonio Silva
ABSTRACT: This article aims to study the importance of in situ camera calibration for the integration of light detection and ranging (LIDAR) and photogrammetric data sets by indirect georeferencing. For this purpose, the in situ camera calibration was performed to estimate the interior orientation parameters (IOP) in the flight condition, using a sub-block of images (six images from two opposite flight strips), extracted from the entire block and a set of LIDAR control points (LCPs) computed by three planes intersection, extracted from the LIDAR point cloud on the building roofs. In order to evaluate the accuracies of the LIDAR and photogrammetric integration, two experiments were performed: the first used IOP from terrestrial calibration, and the second employed the IOP from the in situ calibration. The analysis of the obtained results from the performed experiments showed that the horizontal and vertical accuracies, computed by checkpoints discrepancies, are improved significantly when the IOP from in situ calibration are used. For this condition, the values of horizontal and vertical RMSEs of discrepancies are close to 0.40 and to 0.50 m, respectively.